Assessing the sustainability of Urban Residential Development: An effects based rating - Dick, Courtney (Department of Civil Engineering, 2014)
The effects of historically inefficient urban design have begun to create small negative consequences in urban environments. The aggregation of these small scale changes has led to increasingly recognised large scale impacts. These include, amongst others, climate change, decreasing species diversity, decreasing human health and increasing social inequalities. As the concentrated centres of human activity, urban environments are responsible for the majority of the negative impacts noted. It is not certain to what extent the environmental sinks can assimilate the externalised waste products of the city before a point is reached where the imbalance cannot be corrected. This dissertation investigates what causes the urban environment to operate inefficiently and attempts to provide a manner in which this inefficiency may be recognised and corrected. The particular focus is on mixed income urban residential development in Cape Town, South Africa. This work attempts to develop the theory that effect-based systems of assessment are more useful than traditional technique-based assessment. This may be due to the perceived ease of creation, application and flexibility of effects-based systems. The methodology for this process takes two distinct paths. Firstly it uses extensive literature review to identify urban problems, discuss ideal outcomes and critically assess the systems which attempt to judge these outcomes. Secondly, it attempts to create the new assessment system based on the examination of the evidence from critical review. The success of the processes used in the creation of this assessment system is an important outcome. The assessment system created is tested by applying it to a real development situated in the greater Cape Town area. The findings of this work show that effects-based assessment systems are able to be created and successfully applied. Importantly, it also shows that the methods used to create the system are valid and may be up-scaled in future studies. This work concludes with a detailed review of the outcomes and a set of recommendations for future applications and improvements.